Resisting and surviving the mainstream scientific model: Findings on social relevance and social impact in the tropics. Issue 1 (February 2017) - Wood, Thomaz
The question of the social relevance and social impact of knowledge has gained prominence. However, the debate appears to have been restricted to academia in North America and the United Kingdom, which possess their idiosyncrasies. This study presents and analyses the dual research system of a Brazilian business school that has both applied and scientific research centres and concludes that (a) the development of the applied research centres had its roots in resistance to the introduction of a scientific business school model, (b) scientific research and applied research generate tensions when they coexist alongside one another, (c) the search for social relevance does not require scientific sophistication, and (d) the objective of generating social impact goes beyond achieving social relevance and requires specific competences that are not related to research activity. This study advocates for a critical and moral perspective with regard to the dominant model of scientific production.